Short‐chain fatty acids: Bacterial messengers modulating the immunometabolism of T cells. Issue 6 (17th May 2019) - Luu, Maik; Visekruna, Alexander
Abstract: Short‐chain fatty acids (SCFAs) are mainly generated by bacterial fermentation of non‐digestible carbohydrates such as dietary fiber. In the last decade, new investigations have revealed that SCFAs have a very specific function and serve as active microbial metabolites, which are able to modulate the function of immune cells in the intestine and other tissues. Recent studies have highlighted the immunomodulatory potential of SCFAs in several autoimmune and inflammatory disorders such as multiple sclerosis, colitis, type 1 diabetes and rheumatoid arthritis. While the SCFA‐mediated activation of GPR41/GPR43 signalling pathways and their inhibitory activity on histone deacetylases have been extensively investigated, the impact of SCFAs on the T cell metabolism is poorly understood. SCFAs induce metabolic alterations in T cells by enhancing the activity of the mTOR complex and by regulating their glucose metabolism. Once taken up into T lymphocytes, SCFA‐derived acetyl groups contribute to the cellular acetyl‐CoA pool, which influences the histone acetylation and cytokine gene expression. This article reviews how SCFAs modulate the metabolic status of T cells, thereby impacting on epigenetic modifications and T cell function. We will also discuss how the recent findings from SCFA biology might be utilized for potential immune therapies of various autoimmune diseases. Abstract : Short‐chain fatty acids (SCFAs) have immunomodulatory effects, but the underlying mechanisms are still unclear. Here we discuss how SCFAs modulate metabolic pathways and epigenetic status of murine and human T cells.